2017
DOI: 10.1016/j.semcdb.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of p120ctn family of proteins in central neurons

Abstract: The cadherin-catenin complex in central neurons is associated with a variety of cytosolic partners, collectively called catenins. The p120ctn members are a family of catenins that are distinct from the more ubiquitously expressed α- and β-catenins. It is becoming increasingly clear that the functional roles of the p120ctn family of catenins in central neurons extend well beyond their functional roles in non-neuronal cells in partnering with cadherin to regulate adhesion. In this review, we will provide an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 118 publications
0
29
0
Order By: Relevance
“…Proteins affected by CYP46A1 activation and Cyp46a1 ablation were also different, except CTNND2, DPYSL2, GAP43, MAP1B, MAP6, MARCKS, PKP4, and SAMD14 ( Fig. 6B), which all pertain to neurite growth excluding SAMD14 (122)(123)(124)(125)(126)(127).…”
Section: Brain Phosphoproteomementioning
confidence: 99%
“…Proteins affected by CYP46A1 activation and Cyp46a1 ablation were also different, except CTNND2, DPYSL2, GAP43, MAP1B, MAP6, MARCKS, PKP4, and SAMD14 ( Fig. 6B), which all pertain to neurite growth excluding SAMD14 (122)(123)(124)(125)(126)(127).…”
Section: Brain Phosphoproteomementioning
confidence: 99%
“…The armadillo family member p120ctn has many functions in cells [18,48,49], but its role in vivo remains largely unaddressed. Using a full p120ctn knock-out approach, we found that up to the early stage of gastrulation, mouse development occurs normally in the absence of p120ctn [29].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown or loss of ␦-catenin leads to an increase in excitatory spine density accompanied by an increase of miniature excitatory postsynaptic current frequency (8,9,12). We sought to examine whether calpain-mediated cleavage of ␦-catenin affects the ability of ␦-catenin to regulate dendritic protrusion density in hippocampal neurons.…”
Section: Calpain-mediated Cleavage Of ␦-Catenin Regulates a Subset Ofmentioning
confidence: 99%
“…Furthermore, because the cadherin-catenin complex is linked to the actin cytoskeleton (3), the alterations in the interactions between ␦-catenin and cadherin could, in theory, promote signaling to the actin cytoskeleton thereby influencing protrusion density or stabilization. Similarly, because ␦-catenin associated with cadherin binds to several PDZ domain-containing synaptic proteins (12), it is possible that cleavage of ␦-catenin influences its association with PDZ domain scaffolding proteins thus impacting synapse assembly or disassembly.…”
Section: Proteolysis Of ␦-Catenin In Spine Remodelingmentioning
confidence: 99%
See 1 more Smart Citation